Undetected Severe Fetal Myelosuppression following Administration of High-Dose Cytarabine for Acute Myeloid Leukemia: Is More Frequent Surveillance Necessary? - Jessica Parrott; Marium Holland (Hindawi Limited, 2017)
Background. Cytarabine use during pregnancy carries a 5-7% risk of neonatal cytopenia. We report two cases of fetal myelosuppression following high-dose cytarabine administration for acute myeloid leukemia (AML). Case 1. A 36-year-old G9P6 diagnosed with AML at 21 weeks was monitored for fetal anemia weekly and growth monthly. At 33 weeks (after 2 cycles), BPP was 2/10 and MCA PSV was elevated at 1.51 MoM. Urgent cesarean section was performed. The infant had an initial pH of 6.78 and pancytopenia (hematocrit 13.3%, platelets 3 K/UL, and white blood cell count 2.0 K/UL). Initially transfusion dependent, the neonate had count recovery by 3 weeks. Case 2. A 30-year-old G4P3 with AML at 26 weeks was monitored for fetal anemia twice weekly and growth monthly. At 34 weeks (after cycle 1), she was admitted with neutropenic fever. The fetal MCA PSV was borderline at 1.48 MoM. It improved to 1.38 MoM at 35 weeks but the fetal tracing worsened. At delivery the fetus was found to have a hematocrit of 30%, but with normal platelet and WBC. The fetus did not require any transfusions. Conclusion. Cytarabine use during pregnancy may cause neonatal myelosuppression. We recommend monitoring for fetal anemia with MCA Dopplers twice weekly.